2017
DOI: 10.3899/jrheum.160574
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrillarin Antibodies Are Associated with Native North American Ethnicity and Poorer Survival in Systemic Sclerosis

Abstract: Objective To examine the clinical correlates and survival in patients with anti-fibrillarin antibodies (AFA) in a large international study population consisting of well-characterized systemic sclerosis (SSc) cohorts from Canada, Australia, and the United States of America. Methods Baseline clinical data from the prospective cohorts [Canadian Scleroderma Research Group (CSRG), the Australian Scleroderma Cohort Study (ASCS) and the American Genetics versus Environment in Scleroderma Outcome Study (GENISOS)] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…This association of AFAs with disease severity was independent of the cutaneous form of the disease and remained significant when patients were matched according to their cutaneous form. We also observed a higher proportion of deceased patients in AFA-positive SSc patients, which is consistent with the decreased survival in AFA-positive patients reported in the literature [9,11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This association of AFAs with disease severity was independent of the cutaneous form of the disease and remained significant when patients were matched according to their cutaneous form. We also observed a higher proportion of deceased patients in AFA-positive SSc patients, which is consistent with the decreased survival in AFA-positive patients reported in the literature [9,11].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have described the clinical characteristics associated with AFAs in SSc patients [3][4][5][6][7][8][9][10][11][12]. The estimated frequency of AFAs ranges from 0 to 18.5% of SSc patients, with the highest prevalence found in Afro-American patients [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have been associated with certain HLA-DQB1 alleles, specific ethnicities, such as Afro-Caribbean origin, identify younger SSc patients, and display a higher prevalence of myositis [ 14 , 15 , 19 , 20 ]. It has also been reported that anti-fibrillarin antibodies were associated with native American ethnicity and were mortality independent predictors in those affected with SSc [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analyses of a pooled international cohort did not demonstrate an association of Native North American or Australian Aboriginal heritage with increased mortality. 34…”
Section: Risk Factors For Mortalitymentioning
confidence: 99%